(untitled) - Grinblatt, Mark (New York, 1998)
This text, appropriate for Corporate Finance at either the undergraduate or graduate level, has been written in a way that makes it both intuitive and non-technical. This text, while rigourous, is both practical and very teachable.
Keywords: Financial institutions,Strategic planning,Tổ chức tài chính,Kế hoạch chiến lược; United States,United States,Hoa Kỳ,Hoa Kỳ